Challenges of Refugee Teachers in Malaysian Community-Based Learning Centers - Siah, Poh Chua; Low, Sew Kim; Ho, Khee Hoong; Lim, Yeong Yeong (Makara Human Behavior Studies in Asia, 2020)
Because Malaysia is not a signatory to the 1951 Refugee Convention, the children of refugees living in Malaysia are deprived of any formal education. Children are taught mostly by the refugees themselves, many of whom are volunteers. Most of the community-based learning centers, which encounter many academic and management problems, are also sustained by the refugees. This qualitative study aims to apply the framework of resources and demands theory to explore the work demands encountered by these refugees’ teachers and whether they have enough resources to meet the demands, as the learning centers are self-supported or supported by non-governmental organizations. This study collected data using the focus group method, recruiting participants through purposive sampling. Participants were organized into eight groups, each with seven volunteer participants, and open-ended questions were used for the participants to fully express their views and experiences. The data were analyzed using thematic analysis. The result showed that participants are burdened by academic and administrative tasks, lack of resources, poor infrastructure, and self-incompetence. The findings of the study proposed that more non-government organizations, local communities, and other stakeholders provide expertise and financial assistance to these communitybased learning centers as education is the human right of each child.